Using the ARDL-ECM approach to investigate the nexus between support price and wheat production: An empirical evidence from Pakistan - Chandio, Abbas Ali (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to examine the effect of support price on wheat production in Pakistan during the period 1971–2016. Design/methodology/approach To capture the effect of support price on wheat production, the authors estimated the long-run linkage by using the ARDL bounds testing approach to cointegration. Findings This study confirmed the presence of a positive and long-term effect of area under cultivation, support price and fertilizer consumption on wheat production through ARDL bounds test. The results showed that both in the long run and short run, support price plays an important role in the enhancement of wheat production. The authors also found that the coefficients of the area under cultivation and fertilizer consumption variables were statistically significant and positive both in the long run and short run. Originality/value The use of the ARDL approach that examines the long-run and short-run effects of support price on wheat production in Pakistan makes the current study unique. An emerging economic literature suggests that only limited research has been conducted in this area.